2000
DOI: 10.1128/jvi.74.8.3470-3477.2000
|View full text |Cite
|
Sign up to set email alerts
|

NP and L Proteins of Lymphocytic Choriomeningitis Virus (LCMV) Are Sufficient for Efficient Transcription and Replication of LCMV Genomic RNA Analogs

Abstract: The genome of lymphocytic choriomeningitis virus (LCMV) consists of two negative-sense single-stranded RNA segments, designated L and S. Both segments contain two viral genes in an ambisense coding strategy, with the genes being separated by an intergenic region (IGR). We have developed a reverse genetic system that allows the investigation of cis-acting signals and trans-acting factors involved in transcription and replication of LCMV. To this end, we constructed an LCMV S minigenome consisting of a negative-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
237
1
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(254 citation statements)
references
References 61 publications
8
237
1
8
Order By: Relevance
“…Arenavirus genomic replication requires L and an appropriate NP-encapsidated RNA template (27,28). Although NP is not essential for the catalytic activity of L itself ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Arenavirus genomic replication requires L and an appropriate NP-encapsidated RNA template (27,28). Although NP is not essential for the catalytic activity of L itself ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that at the initial stage of productive infection these proteins might favour virus replication. It was demonstrated that arenavirus N and L proteins are the minimal trans-acting factors necessary to drive transcription and replication of minireplicons (Lee et al, 2000;Ló pez et al, 2001). However, the cellular proteins involved in viral RNA synthesis remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LCMV is the prototype arenavirus; its genome includes two RNA segments, L and S, that use an ambisense strategy for gene expression. The L segment encodes the 90 amino acid Z protein, a zinc-finger protein implicated in budding (Pérez et al, 2003;Salvato et al, 1992), and the L protein, the RNA-dependent RNA polymerase, of 2210 amino acids (Fuller-Pace & Southern, 1989;Lee et al, 2000;Lopez et al, 2001;Singh et al, 1987). The S segment encodes the glycoprotein precursor (GP-C) and the nucleoprotein (NP) (Buchmeier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%